Detection of a New Strain of Wolbachia pipientis in Phlebotomus perfiliewi transcaucasicus, a Potential Vector of Visceral Leishmaniasis in North West of Iran, by Targeting the Major Surface Protein Gene. - Parviz Parvizi; Farzaneh Fardid; Somaieh Soleimani (Tehran University of Medical Sciences, 2013)
Background: Wolbachia pipientis is maternally inherited endoparasitic bacterium belonging to the α-proteobacteria, infecting 20-75% of all insect species including sand flies. The Wolbachia surface protein (wsp) was employed as an appropriate marker for strain typing. The objective of our research was to find the possibility of detection of W.pipientis in Phlebotomus perfiliewi transcaucasicus. Methods: Individual sand flies were screened for the presence of W. pipientis. The obtained sequences were edited and aligned with database sequences to identify W. pipientis haplotypes. Results: T wo haplotypes of W. pipientis were found in P. perfiliewi transcaucasicus. The common haplotype of W. pipientis was found to be identical to the sequences of those submitted in GenBank. New strain (haplotype) of W. pipientis was found novel. The sequence of new strain of W. pipientis occurs in P. perfiliewi transcaucasicus is very different from those already submitted in GenBank. Conclusion: Finding one genetically modified new strain of W. pipientis in P. perfiliewi transcaucasicus, now we can conclude that further documents and studies need to reach the role of cytoplasmic incompatibility of W. pipientis through wild sand fly populations to drive a deleterious gene into and to reduce the density of natural populations of Sand flies.